Generación de métricas en análisis de datos - Bolaños, Fabricio (2002)
In this work we introduce primary generators of metrics, that consist of linear combinations of known metrics. We establish some theoretical properties of these generators, related to the computation of principal components, principal correlations and inertia (generalized variance). We apply primary generators in Principal Component Analysis using some combinations of classic metrics.